Defects of CTLA-4 Are Associated with Regulatory T Cells in Myasthenia Gravis Implicated by Intravenous Immunoglobulin Therapy. (14th February 2020) - Xu, Wenhua; Ren, Mingshan; Ghosh, Swagata; Qian, Kai; Luo, Zhaofeng; Zhang, Aimei; Zhang, Cuiping; Cui, Jiajun
Abstract : Myasthenia gravis (MG) is a CD4 + T cell-dependent autoimmune disease resulting from aberrant immune response mediated by circulating autoantibodies at the neuromuscular junction. Intravenous immunoglobulin (IVIg) is an expensive and commonly used immunotherapeutic approach to treat patients with MG. The mechanisms of actions involved in IVIg treatment, however, remain to be investigated. In an effort to examine the roles of various subsets of CD4 + T cells in the periphery blood of MG and uncover the mechanisms that contribute to the therapeutical effects of IVIg, we first demonstrated that a subset of CD4 + T cells, CTLA-4-expressing regulatory T (Treg) cells, were underrepresented and functionally defective in MG patients. The dynamic profiling during the IVIg therapy course further revealed an inverse relationship between the frequency of CTLA-4 + Treg and the quantitative MG (QMG) score that represents disease severity. Our mechanistic studies indicated that IVIg expands CTLA-4-Treg cells via modulating antigen-presenting dendritic cells (DCs). To determine the molecular defects of CTLA-4 in abnormities of Treg in MG patients, we demonstrated hypermethylation at -658 and -793 CpGs of CTLA-4 promoter in MG Tregs. Interestingly, IVIg therapy significantly reduced the methylation level at these two sites in MG patients. Overall, our study may suggest a role of CTLA-4 in functionally defected Treg cells in MG and its actions involved in IVIg therapy.